2022
DOI: 10.1177/21650799221111300
|View full text |Cite
|
Sign up to set email alerts
|

Drowsy Driving Among Nurses: Potential Impetus to Support Napping

Abstract: Background: As shift workers, nurses are at an increased risk of drowsy driving because of long hours at work and/or short sleep periods between shifts. Methods: In this study, a descriptive cross-sectional cohort design was used to examine the prevalence of drowsy driving among nurses. Findings: An electronic survey was sent to 7,217 nurses of which 2,205 (30.5%) completed the survey. Thirty percent (672 nurses) reported having dozed off while driving during their commute to work. In addition, 44.6% (976) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Finally, nurses also commonly work in shifts that include early mornings, late nights, and rotating schedules [ 76 , 77 ]. Shift work can result in fatigue, reduced alertness, and disrupted sleep patterns, which may increase the likelihood of drowsy driving and impaired driving performance [ 16 , [78] , [79] , [80] ]. The emergence of our final construct, namely drowsy driving, highlights this point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, nurses also commonly work in shifts that include early mornings, late nights, and rotating schedules [ 76 , 77 ]. Shift work can result in fatigue, reduced alertness, and disrupted sleep patterns, which may increase the likelihood of drowsy driving and impaired driving performance [ 16 , [78] , [79] , [80] ]. The emergence of our final construct, namely drowsy driving, highlights this point.…”
Section: Discussionmentioning
confidence: 99%
“…This is because fatigue can impair the neural pathways that control the body's alertness response [ 83 ], leading to impaired decision-making and difficulty concentrating Additionally, the lack of sleep can lead to microsleeps, which can further reduce alertness and increase the risk of an accident [ 84 ]. Previous studies have shown that nurses are at increased risk of drowsy driving due to their work-related fatigue [ 26 , 79 , 85 ].…”
Section: Discussionmentioning
confidence: 99%

Snooze for safety

Weaver,
Camiling-Burke,
Marcus-Aiyeku
et al. 2024
Nursing Management